A NONLINEAR ELECTROMECHANICAL PENDULUM ARM WITH A NONLINEAR ENERGY SINK CONTROL (NES) APPROACH - Alisverisci, G. Fusun; Bayiroglu, Huseyin; Palacios Felix, Jorge Luis; Balthazar, Jose M.; Rebello da Fonseca Brasil, Reyolando Manoel Lopes (POLISH SOC THEORETICAL & APPLIED MECHANICS, 2016)
This paper considers the nonlinear dynamics of an electromechanical device with a pendulum arm and a Nonlinear Energy Sink (NES) put on the point of the pendulum suspension. It is shown that the (NES) is capable of absorbing energy from the system. The numerical results are shown in a bifurcation diagram, phase plane, Poincare map and Lyapunov exponents.
Keywords: nonlinear electromechanical system; bifurcations; nonlinear energy sink; OSCILLATORS; DYNAMICS; Mechanics